Efficiency Analysis of A 3-Phase Induction Motor using a Variable Speed Drive as a Speed Controller at PT. Indonesia Asahan Aluminum - Muchamad Affan; Parlin Siagian; Dino Erivianto (Jurnal Info Sains : Informatika dan Sains, 2026)
This paper analyzes the efficiency performance of a 7.5 kW three-phase induction motor controlled by a Variable Speed ​​Drive (VSD) for industrial speed regulation applications. The motor is rated at 380 V, 50 Hz, four poles, with a nominal speed of 1440 rpm. A constant voltage-to-frequency (V/f) control strategy is implemented with operating frequencies varying from 30 Hz to 50 Hz. Simulation-based analysis is conducted to evaluate electrical input power, mechanical output power, rotational speed, torque, and efficiency under different operating conditions. The results show that the motor input power decreases from approximately 8.0 kW at 50 Hz to 4.0 kW at 30 Hz, indicating significant energy-saving potential during partial-speed operation. Motor efficiency increases with frequency, ranging from 80.0% at 30 Hz to a maximum of 88.8% at the rated frequency. The reduced efficiency at lower frequencies is mainly attributed to the dominance of constant losses such as core and mechanical losses. The study confirms that VSD-based speed control improves operational flexibility and enhances energy efficiency of three-phase induction motors, making it suitable for industrial applications with variable load and speed requirements.